Microbial Ecology of Hospital Surfaces of Maternities in the Public Hospitals of Lubumbashi in the Democratic Republic of Congo: A Cross-sectional Descriptive Study - Hendrick, Mbutshu Lukuke; Françoise, Malonga Kaj (Current Innovations in Medicine and Medical Science Vol. 10, 2022)
The objectives of this chapter were to identify the nature of the germs present on hospital surfaces and to assess their resistance to the antibiotics used in clinical practice in the maternities of public hospitals in Lubumbashi. Germs have the ability to contaminate things, medical equipment, and chemicals in healthcare settings, which then come into touch with exposed anatomical regions. The cross-sectional descriptive study was carried out in seven maternities in January 2015. These maternities were chosen according to whether they met the inclusion criteria. Data collection was performed by swab onsurfaces usingISO/DIS 14698-1 standard.The analysis of the samples was carried out in the laboratory of the university clinics of Lubumbashi. Out of 77 samples of surfaces taken and analyzed, 47 surfaces or 61% presented one or more germs. Candida albicans was more isolated on 20 surfaces, i.e. 43%, followed by Escherichia coli on 17 surfaces (36%), Staphylococcus aureus on 4 surfaces (9%) and Pseudomonas aeruginosa, Klebseiella oxytoca, Enterococci faecalis respectively on 2 surfaces (4%). Les Klebseiella oxytocawas found in Dakin's solution reserved for disinfection in the operating room. LThe germs were multi-resistant to several antibiotics commonly used clinically in all these maternities, in particular to Amoxyciline, Ampicillin and Augmentin (Amoxiciline + clavulanic acid). On hospital surfaces, we discovered a high amount of multiresistant germs. A sound policy for the use of antibiotics and disinfectants must be established, and biocleaning must be improved.